2014
DOI: 10.1007/s00420-014-0983-0
|View full text |Cite
|
Sign up to set email alerts
|

Office workers with high effort–reward imbalance and overcommitment have greater decreases in heart rate variability over a 2-h working period

Abstract: The results indicate that participants exposed to high levels of ERI and overcommitment exhibited a more adverse cardiovascular response (a greater decrease in HRV throughout the 2-h measurement period) compared to their colleagues with lower levels of these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 24 publications
4
23
0
2
Order By: Relevance
“…These variables are used as markers of potential psychobiological pathways mediating stressful experience with disease development. They include studies with experimental or cross-sectional design, where cardiovascular (six reports) [ 32 , 33 , 34 , 35 , 36 , 37 ], immune (three reports) [ 38 , 39 , 40 ] and hormonal parameters (seven reports) [ 32 , 41 , 42 , 43 , 44 , 45 , 46 ] were analyzed. As one report analyzed two different psychobiological markers [ 32 ] the number of studies presented in Table 1 is 27 instead of 28.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These variables are used as markers of potential psychobiological pathways mediating stressful experience with disease development. They include studies with experimental or cross-sectional design, where cardiovascular (six reports) [ 32 , 33 , 34 , 35 , 36 , 37 ], immune (three reports) [ 38 , 39 , 40 ] and hormonal parameters (seven reports) [ 32 , 41 , 42 , 43 , 44 , 45 , 46 ] were analyzed. As one report analyzed two different psychobiological markers [ 32 ] the number of studies presented in Table 1 is 27 instead of 28.…”
Section: Resultsmentioning
confidence: 99%
“…In this latter study an association of OC with increased basal sympathetic drive was observed [ 34 ]. A recent report observed significant effects of both components, ERI and OC, on reduced heart rate variability [ 35 ]. Two further publications introduced fibrinolysis and blood coagulation respectively as potential stress-related biological markers [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study targeting men workers at age of 40 or high in the manufacturer showed that SDNN was significantly decreased in areas of job demand, job insecurity and interpersonal conflicts in the group of high job stress [ 8 ]. The study associated with area of lack of reward, Garza et al reported that effort-reward imbalance was associated with decreases in SDNN, RMSSD and HF and increases in LF/HF ratio [ 40 ]. And study of Kim et al reporting that monthly income was one of factors affecting psychosocial stress and fatigue of firefighters [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results also showed that the use of No, Low Garza et al [37] compared Strong and Very Strong CF and excluded data obtained via the Very Strong CF due to "significant difference in output" between them, although the methodology followed or results were not described. Similar to the findings reported by Garza et al [37] the Very Strong CF was not appropriate to eliminate artefacts in the present study. It is thus important for within study repeatability to keep the CF consistent and to report the specific CF used, for study comparisons.…”
Section: The Influence Of Different Correction Factors On Heart Rate mentioning
confidence: 99%
“…Limited information exists about the effect of using the various CF available in HRV analysis software to automatically correct artefacts [6,37] as well as the species-specific repeatability and reliability of HRV quantification, especially for horses. Repeatability depicts the variation in replicated measurements in the same animal under equivalent situations.…”
Section: Introductionmentioning
confidence: 99%